GAMIFICATION APPROACH IN SUSTAINABLE E-LEARNING METHOD - Ravindran, Dr. D.; Arul Senthil, Dr. B. (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
This paper aims to address various teaching methods to teach the subject effectively. The learning curriculum should involve participation from both the learner and the teacher. Teaching is not a one-sided endeavor. The instructors’ primary duties extend beyond simply imparting knowledge; they also entail that the students understand what has been taught. Different courses require different teaching methods. For. eg. Management education needs to use case study methods, business simulations, management games, etc. Therefore, researchers have discussed different teaching methods, especially gamification.